Regulatory T and B cells in transient hypogammaglobulinemia of infancy - Emsen, Ayça; Uçaryılmaz, Hülya; Güler, Tuğba; Artaç, Hasibe (The Turkish Journal of Pediatrics, 2022)
Background. Transient hypogammaglobulinemia of infancy (THI) is a heterogeneous disorder caused by an abnormal delay in reaching normal IgG levels in the first three years of life. Although THI is a common primary immune deficiency, its pathogenesis has not been fully elucidated. We aimed to investigate the role of regulatory T cells (Tregs) and B cells (Bregs) in the pathogenesis of THI. Methods. T and B cell subsets were evaluated in 40 patients with THI aged 6-41 months and 23 healthy controls aged 6-51 months using flow cytometry. CD4 and interleukin-2 receptor-α alpha (CD25) expression and a lack of interleukin-7 receptor-α (CD127) were used for Treg identification. FoxP3 expression in Tregs was determined as a percentage and mean fluorescence intensity. B cell subsets (plasmablast, mature naive, primarily memory, new memory) and Bregs were defined according to CD19, CD38, and CD24 expressions. Results. Patients with THI (15 females and 25 males; mean age: 18.8 ± 8.6 months) and controls (10 females and 13 males; mean age: 22.6 ± 13.1 months) participated in this study. While the proportion of Tregs of children with THI were significantly increased compared to the controls, primarily memory B cells were reduced. Additionally, the proportions of CD127 in CD3+ and CD3+CD4+ T cells were significantly reduced in the patients with THI compared to the control. No significant difference was detected in the FoxP3 expression of Tregs and the frequency of Bregs in the children with THI. Conclusions. Increased Tregs and decreased primarily memory B cells may cause antibody production delay in children with THI. Changes in the T and B cell compartments may be related to chronic immune activation and affected cellular immunity in THI. Further studies are needed to use T and B cell subsets in the prediction of IgG level recovery.
Keywords: regulatory B cells; regulatory T cells; transient hypogammaglobulinemia of infancy